Parable of Talents: How North Korea-related, Faith-Based Workers Respond to Enhanced Sanctions and a Global Pandemic - Yi, Joseph (Journal of Korean religions, 2022)
How did American members of North Korea-related, faith-based organizations (FBOs)— “US humanitarian evangelicals”—respond to the governmental restrictions linked to enhanced sanctions and a global pandemic? More-committed members shifted from direct person-to-person engagement inside North Korea to indirect activities outside, including political advocacy in the US and language training in South Korea. They articulated narratives that competed with those of human-rights evangelicals supporting increasing sanctions and of fellow humanitarian evangelicals discouraged from North Korea. They cast young North Koreans as victims of sanctions and vanguards of unification, and the current, restrictive period as a “parable of talents” moment to faithfully prepare for God’s special plan for Korea. Our findings derive from a nearly four-year (2018–2021) study of US humanitarian evangelicals, based in South Korea and the US. This article draws on and contributes to the literature on non-governmental organizations aiding North Korea, and to the larger literature on cultures, frames, and narratives.